Pengaruh Model Pembelajaran Matematika Knisley terhadap Pemahaman Konsep Matematis Siswa Kelas X - Juita Inganta Cicio Br Ginting; Mangaratua M Simanjorang (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to determine the effect of the Knisley mathematics learning model on the understanding of mathematical concepts in class X SMA Negeri 2 Kabanjahe. This research was conducted using a sample of 2 classes, namely the Experiment class and the Control class. The form of test that is tested on students is an initial test (pretest), then the researcher provides treatment in the experimental teaching class using the Knisley Mathematics Learning Model and in the control class using the direct learning model, Then a posttest was given to both classes. The data obtained were analyzed using the t test. The results showed that the pretest average in the experimental and control classes was the same as tested using the average similarity test (two-way test) and met namely so accepted. For the posttest average equality test (right side test), it was concluded that the posttest average in the experimental class was greater than the control class because it met the requirements, namely 11.6111559 > 1.66907, so was rejected and the conclusion was obtained that there was an influence Knisley's mathematics learning model for understanding mathematical concepts for class X.